Teachers as Rural Educators. - Kristiansen, Andrew (Alberta Journal of Educational Research, 2015)
In the article, education is seen as a hierarchical cultural encounter between urban and rural values and ways of life. Good teachers do not only deliver curriculum, they also consider the needs and values of their students, as well as those of the local community. The article discusses how teachers’ competence, knowledge and attitudes can affect their teaching, and how attitudes may influence teachers’ approaches towards educational matters in rural settings. It examines some of the challenges teachers are up against if they are to integrate local culture, values and norms in national educational programs, in order to enhance a shared understanding of goals and intentions. I argue that rural schools need to develop pedagogical approaches to teaching and learning that consider rural settings. Cet article présente l’éducation comme une rencontre culturelle hiérarchique entre les valeurs et les modes de vie urbains et ruraux. Les bons enseignants ne font pas que livrer un curriculum, ils tiennent compte des besoins et des valeurs de leurs élèves et de la communauté locale. L’article traite de la façon dont la compétence, les connaissances et les attitudes des enseignants peuvent affecter leur enseignement, ainsi que la mesure dans laquelle les attitudes peuvent influencer les approches qu’ont les enseignants face aux enjeux éducatifs dans les milieux ruraux. L’article examine quelques uns des défis qu’affrontent les enseignants en voulant intégrer la culture, les valeurs et les normes locales dans les programmes pédagogiques nationaux pour appuyer une vision commune des objectifs et des intentions. Je maintiens que les écoles rurales doivent développer des approches à l’enseignement et l’apprentissage qui tiennent compte des milieux ruraux.